Effect Application of Technique Partial Rootzone Drying (PRD) on the Growth, Yield and Quality of Tomatoes - Idris, Muhammad; Hutagaol, Dermawan; Ani, Nurma (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
The research was conducted to evaluate the performance of tomatoes varieties on growth, yield and quality through the application of partial rootzone drying. The study was conducted in green house at the Faculty of Agriculture Universitas Islam Sumatera Utara (UISU) Medan in May 2014 until September 2014. The planting media used were straw compost mixed with top soil enriched withUrea, SP ─ 36 and KCL fertilizer filled into polybeg up to 10 kg in weight. Observation variables are: the growing, yield  and quality of tomato